Sprouty4 correlates with favorable prognosis in perihilar cholangiocarcinoma by blocking the FGFR-ERK signaling pathway and arresting the cell cycle - Qiu, Bo (EBioMedicine, 2019)
BACKGROUND: Perihilar cholangiocarcinoma (PHCC) is the most common subtype of cholangiocarcinoma(CCA). We previously investigated the expression pattern of Sprouty(SPRY) in intrahepatic cholangiocarcinoma(ICC), but the expression and clinical significance of SPRY family members in PHCC are still unknown. METHODS: The expression of SPRY family members(SPRY1-4) was detected in different subtypes of CCA and corresponding adjacent tissues. SPRY4 expression in 142 cases of PHCC was detected by immunohistochemistry, and its clinical significance was evaluated using univariate and multivariate analyses. The functions of SPRY4 in the FGFR-induced proliferation and migration of PHCC cells were investigated through in vitro and in vivo experiments. We further investigated the effects and mechanisms of SPRY4 on FGFR-induced ERK phosphorylation and cell cycle distribution in the presence of FGFR and ERK inhibitors. FINDINGS: SPRY4 was the only SPRY family member associated with PHCC prognosis, and it was identified as an independent factor predicting favorable prognosis. In PHCC, SPRY4 expression was extensively associated with FGFR2, and its expression can be induced by ectopic FGFR2 activation. Through in vitro and in vivo experiments, we demonstrated that SPRY4 suppressed FGFR-induced proliferation and migration by inhibiting ERK phosphorylation. Moreover, SPRY4 knockdown was shown to decrease the percentage of cells in the G1 phase and promote the percentage of cells in the S and G2/M phases by increasing cyclin D1 expression, which also required FGFR-induced ERK phosphorylation. INTERPRETATION: High expression of SPRY4 was an independent biomarker of favorable prognosis in PHCC. SPRY4 expression can be induced by ectopic FGFR2 activation in PHCC. SPRY4 arrested the cell cycle at G1 phase and suppressed FGFR-induced proliferation and migration by inhibiting ERK phosphorylation, indicating that SPRY4 may be a potential therapeutic target in PHCC.